2023
DOI: 10.1007/s00415-023-12135-w
|View full text |Cite
|
Sign up to set email alerts
|

Baseline serum neurofilament light chain levels differentiate aggressive from benign forms of relapsing–remitting multiple sclerosis: a 20-year follow-up cohort

Pablo Arroyo Pereiro,
Albert Muñoz-Vendrell,
Isabel León Moreno
et al.

Abstract: Background and objectives Serum biomarkers are emerging as useful prognostic tools for multiple sclerosis (MS); however, long-term studies are lacking. We aimed to evaluate the long-term prognostic value of the serum levels of neurofilament light chain (NfL), total tau, glial fibrillary acidic protein (GFAP), and chitinase 3-like-1 (CHI3L1) measured close to the time of MS onset. Methods In this retrospective, exploratory, observational, case and controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…A meta-analysis of eight studies evaluating sGFAP in 776 PwMS and 348 HCs revealed a statistically significant increase in sGFAP in PwMS compared to in the HCs (SMD = 0.54, 95% CI: 0.1 to 0.99, p-value = 0.02, I 2 = 90%) (Figure 2B). [11,14,15,18,[36][37][38][39]41,42,[44][45][46], (B) serum sample [14,49,54,57,63,64,66,71].…”
Section: Comparison Of the Gfap Level Between Ms And Hcsmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of eight studies evaluating sGFAP in 776 PwMS and 348 HCs revealed a statistically significant increase in sGFAP in PwMS compared to in the HCs (SMD = 0.54, 95% CI: 0.1 to 0.99, p-value = 0.02, I 2 = 90%) (Figure 2B). [11,14,15,18,[36][37][38][39]41,42,[44][45][46], (B) serum sample [14,49,54,57,63,64,66,71].…”
Section: Comparison Of the Gfap Level Between Ms And Hcsmentioning
confidence: 99%
“…According to the meta-analysis of six studies measuring the sGFAP level of 265 PMS and 490 RRMS patients, a significantly increased sGFAP was found in PMS patients compared to in RRMS patients (SMD = 0.5, 95% CI: 0.25 to 0.75, p-value < 0.001, I 2 = 53%) (Table 2). [11,14,15,18,[36][37][38][39]41,42,[44][45][46], (B) serum sample [14,49,54,57,63,64,66,71].…”
Section: Comparison Of the Gfap Level Between Pms And Rrmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high variability of MS, in which the disease can manifest very differently between individuals and over time in the same patient, clinical and radiological markers may not be specific or sensitive enough to capture the full range of changes in terms of inflammation and neurodegeneration ( 7 ). Assessment and quantification of inflammatory activity and neurodegeneration are essential to establish the severity of the disease, the long-term prognosis, the need for treatment, the treatment option and the individual response to the selected treatment, as well as the achievement of therapeutic goals ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%